1984
DOI: 10.1128/aem.48.5.984-987.1984
|View full text |Cite
|
Sign up to set email alerts
|

Role of stagnation and obstruction of water flow in isolation of Legionella pneumophila from hospital plumbing

Abstract: The stagnation of water in two of four hospital hot-water storage tanks found to contain Legionella pneumophila was reduced by keeping the two tanks continually on-line for 1 year. L. pneumophila colony counts in these two tanks fell quickly to low levels, whereas the organisms persisted in the two tanks that were not in use. L. pneumophila continued to be isolated from 50 to 100% of the hospital showerheads which were sampled during this period. We also examined aerators and other hospital faucet fixtures whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 19 publications
(16 reference statements)
3
49
0
2
Order By: Relevance
“…Stagnation within water systems has been cited by numerous authors as a condition favouring Legionella replication (Ciesielski et al 1984;Harper 1988;Anon 1996). However, the effect of low flow conditions on the presence of Legionella in a water system has not been scientifically evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stagnation within water systems has been cited by numerous authors as a condition favouring Legionella replication (Ciesielski et al 1984;Harper 1988;Anon 1996). However, the effect of low flow conditions on the presence of Legionella in a water system has not been scientifically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that have been linked to Legionella colonization in water distribution systems include hot water temperature, age and configuration of the system and calcium concentration (Plouffe et al 1983;Vickers et al 1987;Colbourne et al 1988;Alary and Joly 1992). Stagnation is also widely believed to be a predisposing factor for colonization (Ciesielski et al 1984). For example, Ciesielski et al found that the concentration of Legionella was reduced from 100 CFU ml )1 to an undetectable level (<10 CFU ml )1 ), when stagnant hot water tanks were brought back into service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once contamination is established, multiplication of L. pneumophila may be influenced by environmental factors. Accumulation of sediment in stagnant water, relatively low temperature in hot water systems and low concentration of free chlorine have been linked to contamination (Ciesielski et al, 1984;Editorial, 1983;Kuchta, et al, 1983). The presence of organic compounds and other bacteria in the sediment have also been identified as amplifying or synergistic factors in experimental studies (Wadowsky et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…1981 ; Dennis et al. 1982;Ciesielski et al 1984). Water held in pipes between a circulating supply and an outlet (deadlegs) can provide a suitable environment for the proliferation of legionellas, which when disseminated as aerosols from taps and showers have been linked with Legionnaires' disease (Bartlett & Bibby 1983;Bartlett et al 1984; Neil1 et al.…”
Section: Introductionmentioning
confidence: 99%